MicroRNA-320a Promotes Epithelial Ovarian Cancer Cell Proliferation and Invasion by Targeting RASSF8 - Zhang, Lili; Chen, Huixiao; He, Fengxi; Zhang, Shiqian; Li, Aihua; Zhang, Aifeng; Zhang, Anqi (Frontiers in Oncology, 2021)
MicroRNAs (miRNAs) play important roles in tumorigenesis by controlling target gene expression. With opposing roles as a tumor suppressor or oncogene, microRNA-320a (miR-320a) was found to participate in tumor genesis and progression and also identified as a potentially useful marker in cancer diagnosis, treatment, and prognosis. To better understand the role of miR-320a in ovarian cancer, we investigated miR-320a expression in epithelial ovarian cancer (EOC) specimens as well as EOC cell lines and analyzed correlations between miR-320a expression and processes associated with EOC progression. The miR-320a level in EOC specimens was found to be associated with ovarian cancer progression and infiltration. Through in vitro and in vivo studies, we found that miR-320a significantly promoted the proliferation, migration, and invasion of EOC cells, and we identified RASSF8 as a target gene of miR-320a that was downregulated in EOC tissues and cell lines. In vitro downregulation of RASSF8 promoted the growth, migration, and invasion of EOC cells. Together these findings indicate that RASSF8 is a direct target of miR-320a, through which miR-320a promotes the progression of EOC.